2021
DOI: 10.3390/vaccines9070707
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Diabetes Patients’ Practice, Knowledge and Attitudes towards Influenza Immunization

Abstract: Diabetic patients are at higher risk of developing infectious diseases and severe complications, compared to the general population. Almost no data is available in the literature on influenza immunization in people with type 1 diabetes mellitus (T1DM). As part of a broader project on immunization in diabetic patients, we conducted a cross-sectional study to: (i) report on seasonal influenza coverage rates in T1DM patients, (ii) explore knowledge, attitudes, and practices (KAPs) towards seasonal influenza in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…This suggests that the coverage rate of the elderly may be influenced by younger people in the family or caregivers. 40 In line with the findings of the current study, other surveys have indicated the critical role that higher education level plays in promoting vaccination coverage and willingness. 33 , 37 , 41 Higher education level continues to be a key driver of raising utilization of health care.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the coverage rate of the elderly may be influenced by younger people in the family or caregivers. 40 In line with the findings of the current study, other surveys have indicated the critical role that higher education level plays in promoting vaccination coverage and willingness. 33 , 37 , 41 Higher education level continues to be a key driver of raising utilization of health care.…”
Section: Discussionsupporting
confidence: 91%
“…Sixty-one studies reported perceived barriers to receiving an influenza vaccination in the total population ( Table 4 ) [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
“…The perceived barriers specific to the unvaccinated population were assessed in 20 publications. Similarly, social barriers were most commonly investigated (N = 67), although the unvaccinated population most frequently reported a perceived lack of knowledge of influenza vaccines (32.3%) [ 16 , 19 , 21 , 23 , 24 , 31 , 34 , 37 , 41 , 45 , 46 , 47 , 57 , 58 , 60 , 68 , 69 , 75 , 77 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations